PEDF-Expressing mesenchymal stem cells restore ovarian function via Tim-3-Mediated immune modulation in primary ovarian failure - Seyida Yimamuyushan; Song Shi; Aikeremujiang Muheremu; Jinling Yi (Journal of Ovarian Research)
Abstract Background Primary ovarian failure (POF), characterized by premature ovarian dysfunction, remains a therapeutic challenge due to limited interventions addressing its immune dysregulation. Regulatory T cells (Tregs) and immune checkPOFnt pathways, such as Tim-3, are critical yet underexplored targets. Pigment epithelium-derived factor (PEDF), an immunomodulatory protein, offers promise for enhancing mesenchymal stem cell (MSC) therapy in POF. Methods Using a cyclophosphamide-induced POF mouse model, we evaluated the therapeutic potential of PEDF-overexpressing bone marrow MSCs (BMSCs-PEDF). Mice were stratified into PBS, adenovirus-delivered PEDF (AD-PEDF), control BMSCs (BMSCs-LacZ), and BMSCs-PEDF groups. Outcomes included ovarian index, follicular histology, Treg cell populations, Tim-3/Gal-9 expression, and serum hormone/cytokine profiles. Results BMSCs-PEDF outperformed other treatments, significantly restoring estrous cyclicity (2.1-fold increase in vaginal exfoliated cells vs. AD-PEDF, P < 0.05) and ovarian index (1.8-fold higher vs. AD-PEDF, P < 0.01). Histology revealed a 3.5-fold increase in viable follicles, with reduced atresia. Mechanistically, BMSCs-PEDF expanded Tim-3 + CD4 + CD25 + Tregs (4.2-fold vs. PBS) and upregulated ovarian Tim-3/Gal-9 expression (3.7-fold vs. AD-PEDF, P < 0.001), correlating with suppressed IFN-γ (62% reduction) and restored estrogen (2.4-fold increase) and progesterone levels. Conclusion This study demonstrates that PEDF-engineered BMSCs rejuvenate ovarian function by dual mechanisms: enhancing Treg-mediated immune tolerance via the Tim-3/Gal-9 axis and promoting follicular survival. These findings position BMSCs-PEDF as a transformative, mechanism-driven therapy for POF, with broad implications for autoimmune-related infertility.